Legal Renewal on the Protection of Human Trafficking Victims Based on Access to Justice in Efforts to Fulfill the Rights of Restitution and Rehabilitation in Indonesia - Tito Laragatra; Ilham Prisgunanto; Kif Aminanto (Indonesian Journal Publisher, 2026)
Human trafficking is an organized transnational crime that not only violates criminal law but also constitutes a form of human rights violation because it eliminates the freedom, security, and dignity of victims through sexual exploitation, forced labor, child trafficking, digital exploitation, and various other forms of exploitation. This study aims to analyze the weaknesses in regulations and implementation of legal protection for victims of human trafficking in Indonesia and to formulate a reconstruction of legal reform based on access to justice in fulfilling the rights of restitution and rehabilitation of victims. This study employs a normative juridical method with a legislative approach and a conceptual approach through an analysis of Law Number 21 of 2007 concerning the Eradication of the Crime of Human Trafficking, Law Number 31 of 2014 concerning the Protection of Witnesses and Victims, and various international legal instruments such as the Protocol to Prevent, Suppress and Punish Trafficking in Persons, the Convention on the Elimination of All Forms of Discrimination Against Women, and the Convention on the Rights of the Child. The research findings indicate that the protection of human trafficking victims in Indonesia still faces various weaknesses, including the difficulty of implementing restitution, the absence of state compensation funds, weak multidisciplinary rehabilitation, limited legal aid, victim blaming, and a lack of integration of the national victim protection system. Therefore, legal reform is needed through strengthening state compensation mechanisms, establishing an integrated victim protection system, a digital victim monitoring system, strengthening the role of the Witness and Victim Protection Agency, multidisciplinary rehabilitation, and harmonizing national law with international law to achieve more humane, effective, and equitable protection for human trafficking victims based on victim-centered justice.